Suggesting a new combination of antiviral agents: Targeting the Herpes Simplex Virus - Subathra Devi C., Taneesha Chawla, Nida Itrat Abbasi, Nupoor Neha Upadhyay, Mohanasrinivasan V. (Journal of Applied Pharmaceutical Science, 2014)
Herpes simplex is a viral disease caused by herpes simplex virus type 1 and type 2.Several broad spectrum drugs are available but most of the strains developed resistance against it. To overcome this problem, we are suggesting a new combination drug for the treatment of herpes simplex. The main aim of the hypothesis is to formulate a topical drug and an intravenously administered drug against herpes simplex virus. Chebulagic acid and Punicalagin inhibit HSV-1 entry at non-cytotoxic doses in A549 human lung cells. sodium is important to curb the proliferation and cell to cell spread of herpes simplex virus. TA205, an antitalin monoclonal antibody can be microinjected in human fibroblasts. It causes allosteric inhibition on integrin binding to the talin protein FERM domain. Sodium lauryl sulphate is a surfactant which enhances intra epidermal drug delivery without increasing transdermal delivery. Amphipathic DNA polymers work against HIV binding and entry. Candidate topical microbicides are efficient against viral entry and cell to cell spread by binding HSV glycoprotein B. Thus, a combination of the above mentioned drugs can be used to prevent HSV binding, cell to cell spread and infection.
Keywords: HSV, aciclovir, integrin, chebulagic acid, monoclonal antibody.